Spontaneous brain abscess formation: challenge of a shifting pathogen spectrum over the last 21 years – a single center experience - Kraus, Luisa Mona; Overstijns, Manou; Rahal, Amir El; Behringer, Simon; Buttler, Klaus Jürgen; Andereggen, Lukas; Beck, Jürgen; Schnell, Oliver; Hornuss, Daniel; Wagner, Dirk; Cipriani, Debora (Acta Neurochirurgica, 2024)
Background: Spontaneous intracerebral abscess formation is a rare condition presenting with a disabling sequela. The origin of infection can either be primary or secondary to an infection at another location. The site of primary infection - due to the proximity, often the oral cavity, the sinuses, and the orbit - determines the causative pathogens. Treatment often combines surgical and antimicrobial therapies. To determine the microbiology and respective changes and treatment outcome, we performed this retrospective monocentric cohort study of patients requiring surgical treatment of brain abscesses. Methods: Patients undergoing surgical treatment of a primary intracranial abscess between January 2000 and January 2021 in the Department of Neurosurgery, Freiburg University Hospital were included. Demographic, clinical and imaging data were extracted from patients’ medical records and databases. Treatment approaches were also analyzed, and surgical therapy and antibiotic therapy were reported. Outcome was assessed by the modified Rankin score (mRS) and was dichotomized into good (mRS 0–3) and poor (mRS 4–6) outcome. Results: We included 65 patients with spontaneous intracerebral abscess that were treated with neurosurgical intervention at our institution. Analysis of the causative pathogens showed an increasing dominance of rare pathogens such as fungi, parasites, mycobacteria and anaerobes. Outcome measured by the mRS was similar from 2005 to 2021. Conclusions: The pathogen spectrum of spontaneous intracerebral abscess at our institution is shifting with rarer pathogens being increasingly detected. This retrospective analysis highlights the need for microbiological diagnosis and of combined surgical and antibiological treatment.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Intracerebral abscess; Odontogenic infection; Rare pathogens; SAG